U.S. Wine consumer interest in wine ingredient and nutritional information - Terry M. Lease; Deirdre Sommerlad-Rogers (Wine Economics and Policy, 2022)
In the United States, labelling for wine containing at least 7% alcohol by volume is regulated by the Tax and Trade Bureau, which does not require wine labels to include ingredient or nutrition labelling, except for added sulfites. With the European Union moving toward mandatory disclosure of nutrition and ingredient information for wine, one may expect the level of debate in the U.S. to increase. We conducted an online survey of consumers in the U.S. who are at least 21 years old (legal drinking age in the U.S.) and consume wine at least once every two or three months to determine their interest in wineries disclosing ingredient and nutrition information for wine. We asked about the importance of ingredient information when deciding which wine to purchase and when determining willingness to pay, and we asked about the importance of nutrition information when deciding which wine to purchase. We separately regressed three dependent variables against Wine Consumption (frequency), Price, Physical Activity, Diet, Wine Knowledge, Age, Income, and Education. Overall, respondents indicated that having ingredient and nutrition information was only somewhat important, with mean responses 3.04 on a 5-point scale (1 = Not Important, 5 = Very Important) for ingredient information when choosing a wine, 3.01 for ingredient information when determining willingness to pay, and 2.48 for nutrition information when choosing a wine. The factor with the greatest impact on interest in ingredient information was Price, with consumers who buy a higher-end wine at least monthly having a higher level of interest, followed by Diet, with consumers with a healthy diet having a higher interest in ingredient information, and Age, with older consumers having less interest in ingredient information. Price, Diet, and Age also had the greatest impact regarding interest in nutrition information, following the same direction but with Age being the most significant.
Keywords: 330; ingredient and nutrition information; U.S. wine consumers